2020
DOI: 10.1159/000504843
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Characteristics and Trends in Treatment Response of Hidradenitis Suppurativa Patients: A Southern US Cohort Study

Abstract: Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin condition that has a substantial impact on patients' quality of life. As the exact pathogenesis remains unclear, treatment is complex and not yet standardized. Objectives: The aim of this study was to describe patient characteristics and to broadly examine trends in treatment response of various therapeutic strategies in patients with HS in a single academic referral center in the southern USA. Methods: A retrospective chart review was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…8,11 Disease onset typically occurs in young adulthood, and the most commonly affected areas include the groin/genitals, axillae, buttocks and breasts. [12][13][14][15][16] Patients with HS may experience painful lesions, impaired work ability or productivity, reduced sexual health, and feelings of shame and stigmatization, all of which contribute to markedly reduced quality of life (QoL). [17][18][19][20] Furthermore, patients are often burdened by psychological comorbidities that worsen with increasing disease severity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,11 Disease onset typically occurs in young adulthood, and the most commonly affected areas include the groin/genitals, axillae, buttocks and breasts. [12][13][14][15][16] Patients with HS may experience painful lesions, impaired work ability or productivity, reduced sexual health, and feelings of shame and stigmatization, all of which contribute to markedly reduced quality of life (QoL). [17][18][19][20] Furthermore, patients are often burdened by psychological comorbidities that worsen with increasing disease severity.…”
mentioning
confidence: 99%
“…Increased prevalence among black and biracial vs. white individuals has been described in the USA 8,11 . Disease onset typically occurs in young adulthood, and the most commonly affected areas include the groin/genitals, axillae, buttocks and breasts 12–16 . Patients with HS may experience painful lesions, impaired work ability or productivity, reduced sexual health, and feelings of shame and stigmatization, all of which contribute to markedly reduced quality of life (QoL) 17–20 .…”
mentioning
confidence: 99%
“…The relation between HS and alcohol, cannabis and other drug use is still under investigation. Different studies found that alcohol consumption did not impact HS course [ 162 , 163 , 164 ]. Fairly recently, a study on a population of 48 post-surgery Hurley III HS patients observed a slight but statistically significant risk of local recurrences related to alcohol consumption.…”
Section: Hs and Alcohol And Substance Abusementioning
confidence: 99%
“…Furthermore, the proportion of ex-or current smokers in the Danish cohort was 100% and even exceeded the proportion of our patients of 78.6%. This is remarkable in terms of the fact that both, nicotine abuse and abdominal obesity, are known as potential trigger factors for both diseases and occur above average in both HS and Pso [31]. A strong exogenous and endogenous triggering could possibly promote the parallel occurrence of both diseases.…”
Section: Prevalence and Onset Of Diseasementioning
confidence: 99%